Costs and Income in the Norwegian Payment System 2001. An Application of the Activity Based Costing Framework - Olaf Gresvik; Grete Øwre (Norges Bank, 2003)
This paper summarizes a survey of costs and income in the payment system of Norwegian banks in 2001. The cost analysis was carried out by using the activity based costing (ABC) framework. The results from this analysis are presented in the paper, combined with information from other sources to form a complete picture of the costs and income in the retail payment systems run by banks in Norway. The results are compared with results from two previous surveys, performed in 1988/1989 and 1994. The main findings show that the costs have been substantially reduced over time, income based on direct pricing has risen, and although the banks still deliver payment services with a loss, the negative margin has decreased.
hdl:11250/2498619
Keywords: G21; M1; 330; ABC; bank's costs; payment systems costs; retail systems; activity based costing